2017
DOI: 10.1016/j.cjtee.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of epidural and intravenous steroids after percutaneous endoscopic lumbar discectomy for large lumbar disc herniation

Abstract: ObjectiveTo assess the early curative effect of epidural or intravenous administration of steroids during a percutaneous endoscopic lumbar discectomy (PELD).Methods28 consecutive patients who underwent PELD due to large lumbar disc herniation between November 2014 and January 2016 were followed up for 6 months. These patients were divided into two groups according to the treatment they received after PELD. 14 patients (Group A) were treated by PELD and epidural steroids, while the other 14 patients (Group B) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…PELD has become a popular operative procedure for LDH. The clinical outcome has been reported for each operative approach (interlaminar, transforaminal, and posterolateral) [ 6 , 10 , 11 ]. Although previous studies have shown satisfactory clinical results of PELD in hospitalized patients with LDH, and only a few studies reported about the day surgery patients undergoing PELD.…”
Section: Discussionmentioning
confidence: 99%
“…PELD has become a popular operative procedure for LDH. The clinical outcome has been reported for each operative approach (interlaminar, transforaminal, and posterolateral) [ 6 , 10 , 11 ]. Although previous studies have shown satisfactory clinical results of PELD in hospitalized patients with LDH, and only a few studies reported about the day surgery patients undergoing PELD.…”
Section: Discussionmentioning
confidence: 99%
“…PELD has become a popular operative procedure for LDH. The clinical outcome has been reported for each operative approach (interlaminar, transforaminal, and posterolateral), and satisfactory results have already been reported (6,11,12). Although numerous previous studies have shown good clinical results of PELD for hospitalized patients with LDH, there are few articles reporting on the day surgery patients undergoing PELD.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other studies (21,22), in which a similar minimally invasive PELD was performed, the medication method was different. The therapeutic efficacy of "cocktail treatment" should be better than that of single steroid usage; the drugs are delivered through the gelatin sponges, which can exert a more targeted effect on the nerves, raising the local drug concentration and prolonging the action time.…”
Section: E215mentioning
confidence: 95%
“…In consideration of the half-life period of steroids, dexamethasone, a long-acting steroid with a half-life period of approximately 36-54 hours, was selected. Zhang et al (21) proved that patients who underwent PELD with epidural steroid administration for large LDH showed favorable curative effect compared www.painphysicianjournal.com with those who underwent PELD with intravenous steroid administration. In another randomized study, Shin et al (22) observed that epidural steroids after PELD reduced back pain and leg pain while improving functional outcomes in the short-term postsurgical period.…”
Section: E215mentioning
confidence: 99%